"Other psychotherapies": Healing interactions across time, geography, and culture. (December 2020) - White, Ross G.; McGeachan, Cheryl; Miller, Gavin; Xenophontos, Sophia
This article introduces the special issue of Transcultural Psychiatry entitled "Other Psychotherapies": Healing Interactions across Time, Geographies, and Cultures. This special issue is intended to highlight that, rather than being exclusively a modern phenomenon, variants of psychotherapeutic practice have existed for millennia in diverse sociocultural contexts. This article explores the historical development of Western psychotherapy and points to the important contribution that Greco-Roman scholars from antiquity made to contemporary understandings of mental states and emotional wellbeing. The ways in which healing interactions have been localized to reflect the local cultural and geographic contexts are also highlighted through a discussion of recent work in psychotherapeutic geographies. This allows us to identify commonalities and differences between various forms of psychotherapy. We also consider how particular subcultures may influence the future development of psychotherapy. This article serves to foreshadow the themes that are explored in more detail in the collection of articles that make up the "Other Psychotherapies" special issue. The various articles that contribute to the special issue are introduced, and the key issues explored by these articles briefly highlighted. The intention of the special issue is to facilitate an opportunity to appreciate the ways in which psychotherapies are a product of the epoch, setting, and institutions that shape people's lives.